Long-term effects of three commercial cranberry products on the antioxidative status in rats: a pilot study - Palíková, Irena; Vostálová, Jitka; Galandáková, Adéla; Rajnochová Svobodová, Alena; Kosina, Pavel; Večeřa, Rostislav; Stejskal, David; Prošková, Jitka; Hrbáč, Jan; Bednář, Petr; Maier, Vítězslav; Černochová, Drahomíra; et al. (Journal of agricultural and food chemistry, 2010)
Cranberry (Vaccinium macrocarpon Ait. Ericaceae) fruits and juice are widely used for their antiadherence and antioxidative properties. Little is known however about their effects on clinical chemistry markers after long-term consumption. This study was conducted to evaluate the effect of three commercial cranberry products, NUTRICRAN90S, HI-PAC 4.0, and PACRAN on the antioxidative status of rodents, divided into three experimental groups. The products were given as dietary admixtures (1500 mg of product/kg of stock feed) for 14 weeks to male Wistar rats (Groups 2-4) and a control Group 1 which received only stock feed. There were no significant cranberry treatment-related effects on oxidative stress parameters, catalase, glutathione peroxidase, glutathione reductase, glutathione transferase, superoxide dismutase, total antioxidant capacity, thiobarbituric acid reactive substances, advanced oxidation protein products, total SH-groups, or any other measured clinical chemistry markers. Hematological parameters, body weight, and food consumption were also unaffected by intake of cranberries. Only liver glutathione reductase activity and glutathione levels were significantly lower in Group 4 than in Group 1. Plasma alkaline phosphatase alone was significantly decreased in Group 2. No gross pathology, effects on organ weights, or histopathology were observed. No genotoxicity was found, and total cytochrome P450 level in liver was unaffected in all groups. The levels of hippuric acid and several phenolic acids were significantly increased in plasma and urine in Groups 2-4. The concentration of anthocyanins was under the detection threshold. The dietary addition of cranberry powders for 14 weeks was well tolerated, but it did not improve the antioxidative status in rats.
Keywords: Vaccinium macrocarpon; rostlinné přípravky; antioxidancia; Pilot Projects; zvířata; Rats; Antioxidants; Catalase; oxidační stres; mužské pohlaví; Oxidative Stress; glutathionperoxidasa; Rats, Wistar; krysa rodu Rattus; potkani Wistar; katalasa; Animals; Glutathione Peroxidase; Plant Preparations; pilotní projekty; Male